Genre and dramaturgic features of the modern peplum - Kosachova, Olga (ХДАК, 2023)
The problem of genres in film studies is extremely relevant due to its influence on the understanding, analysis and interpretation of films. Genres determine the specificity of films, giving them a defined structural basis, aesthetic and plot frames that influence the viewer’s perception. The peplum genre is one of the most spectacular and difficult to produce in the film industry, so the study of its genre and dramaturgical features will contribute to the optimization of theoretical component of the audiovisual industry and practical component as well.
Keywords: кіножанри; movie genres